EFFECT OF EVENT MARKETING, HOUSING CONCEPT AND LOCATION ON HOME PURCHASE DECISIONS - Tienni Mariana Simanjorang; Eddy Sukandar; Yudiyanto Joko Purnomo (Jurnal Ekonomi, 2023)
The purpose of this study was to determine the impact of event marketing, housing concept and location on home buying decisions at Grand Pinus Regency Bali. The examination procedures used in this study are validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, determination analysis and f-test. The results of the review show that the promotion mix influences the decision to buy a house in Grand Pinus Regency Bali. From the test results with the T test, it shows that event marketing has a significant effect on home buying decisions. The housing concept influences the decision to buy a house in Grand Pinus Regency Bali. From the test results with the T test shows that the concept of housing affects the decision to buy a house. Location has a direct effect on the decision to buy a house in Grand Pinus Regency Bali. From the results of testing with the T test, it shows that location influences the decision to buy a house. Judging from the f-test, it is obtained that F-count > F-table is 212,297 > 3.12, this shows that event marketing, the concept of housing and location basically influence the decision to buy a house with a sig level. Big 0.000 < 0.050.